Asuhan Kebidanan Pada Bayi Baru Lahir Ny. P Di PMB Erida Rismayanti Wilayah Kerja Pusksmas Laboy Jaya - Sari, Gusnita Laila; Harmia, Elvira (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Newborns (BBL) are babies aged 0 to 28 days, in BBL there will be very big changes where BBL undergoes a period of adjustment from life in the womb to life outside the womb (world). Midwives play an important role in the adaptation changes experienced by infants, because during the BBL period they are very susceptible to complications. This research is in the form of an observational descriptive case study conducted at the Independent Practice of Midwife Erida Rismayanti in By. Mrs. P. This research was conducted on July 14-21, 2022, the data collected through observation, interview, examination and documentation techniques. From the results of the case study research given to By. Mrs. P which was carried out for 3 visits, the first visit was carried out at the age of 6 hours BBL in good health, the second visit was carried out at the age of 4 days with complaints of fussiness at night, the third visit was carried out at the age of 8 days BBL was in good health, breastfeeding smoothly, there were no signs danger signs or complications in BBL, as well as the care provided has been running smoothly and safely. It is hoped that midwives can improve the quality of services comprehensively based on their authority in providing services to BBL